Factors Influencing the Prices of Red Chili and Shallots in Indonesia: Analysis of the Impact on the Global Market - Muhammad Ilham Riyadh (International Journal of Social Service and Research, 2023)
Movements in international commodity prices became significant when three stages of crisis occurred in the world economy, namely the world oil price crisis, the global financial crisis and the world food price crisis. This situation can have an impact on Indonesia's economic growth. The objectives of this research are: 1 Do fluctuations in world oil prices affect the prices of chilies and shallots in Indonesia (2) Do fluctuations in the rupiah exchange rate affect the prices of chilies and shallots in Indonesia (3) Do global prices of chilies and shallots influence the prices of chilies and shallots in Indonesi. The information used is secondary time series data from 1980 to 2019 . The food commodities being studied are : world price of chilies and shallots , value Rupiah exchange , price world oil as well price chilies and onions red Domestically , based on estimation results, it shows that international prices such as world oil prices have a significant positive effect on domestic prices of chilies and shallots . The Rupiah exchange rate has a significant positive effect on the price of chilies and shallots in Indonesia, while the world price of chilies and shallots has a negative effect and has no This is significant for the price of chilies and shallots in the country. This is because chilies and shallots are products that are widely produced domestically. Most of the Chilies and Shallots sold in Indonesia are domestically produced, so the prices of Chilies and Shallots in Indonesia are more influenced by production costs and government policies and supply and demand in the Indonesian market. This can be done by improving infrastructure, especially transportation networks and storage facilities. Empowering farmers by providing financial and technical support. Developing different food sources to reduce dependence on limited food sources, and consumer protection with fair prices for consumers as well as providing support for subsidy programs needed to help stabilize food prices